Consumers’ Hedonic, Utilitarian, and Social Values in Smartwatch Purchase Decisions: The Moderating Role of Switching Costs - Liu, Zhengwei; Gantulga, Urandelger; Yadamsuren, Otgonsuren; Ganbold, Munkhbayasgalan (Jurnal Ilmiah Peuradeun, 2025)
Wearable devices, particularly smartwatches, have recently garnered significant consumer interest. However, limited research has explored how consumers’ perceived values influence their intention to continue using this technology. This study seeks to fill this gap by examining the perceived values—hedonic, utilitarian, and social—that drive purchase decisions, with a specific focus on the moderating role of switching costs on repurchase intentions in the context of a developing country: Mongolia. Data were collected through an online questionnaire distributed via Google Forms, resulting in 465 usable responses from potential smartwatch users. The partial least squares (PLS) approach was employed to evaluate the proposed hypotheses. The findings indicate that consumers’ purchase decisions are influenced by hedonic, social, and utilitarian values. Furthermore, switching costs were found to significantly moderate both purchase decisions and repurchase intentions. These results offer valuable insights for smartwatch manufacturers and marketers. By understanding the key factors driving purchase and repurchase decisions, industry stakeholders can develop targeted marketing strategies and product features that cater to consumers’ needs, ultimately improving customer retention and increasing market share in the rapidly expanding wearable technology sector.